Educational strategies to improve adherence to patient identification - Melissa Prade Hemesath; Helena Barreto dos Santos; Ethel Maris Schroder Torelly; Amanda da Silveira Barbosa; Ana Maria Müller de Magalhães
Objective: The aim of this study was to analyze the impact of educational actions on the results of an adherence indicator while checking patient identification wristbands before high-risk care. Methods: This is a descriptive and exploratory study that was conducted in a large university hospital between January 2013 and December 2014, where 6,201 patients were interviewed. Data were analyzed by descriptive statistics. Results: The analysis and monitoring of the adherence indicator in patient identification wristbands showed a tendency to increased percentage along the study period, from 42.9% to 57.8% between January and April 2013,and from 81.38% to 94.37% between September and December 2014. Conclusions: Teaching strategies based on staff awareness improved the professionals' adherence to checking patient ID wristbands. In addition, this result can contribute to strengthening the safety culture within the institution.